A knowledge management system framework for an open biomedical repository: communities, collaboration and corroboration. Issue 10 (30th September 2020) - Kruesi, Lisa; Burstein, Frada; Tanner, Kerry
Abstract : Purpose: The purpose of this study is to assess the opportunity for a distributed, networked open biomedical repository (OBR) using a knowledge management system (KMS) conceptual framework. An innovative KMS conceptual framework is proposed to guide the transition from a traditional, siloed approach to a sustainable OBR. Design/methodology/approach: This paper reports on a cycle of action research, involving literature review, interviews and focus group with leaders in biomedical research, open science and librarianship, and an audit of elements needed for an Australasian OBR; these, along with an Australian KM standard, informed the resultant KMS framework. Findings: The proposed KMS framework aligns the requirements for an OBR with the people, process, technology and content elements of the KM standard. It identifies and defines nine processes underpinning biomedical knowledge – discovery, creation, representation, classification, storage, retrieval, dissemination, transfer and translation. The results comprise an explanation of these processes and examples of the people, process, technology and content dimensions of each process. While the repository is an integral cog within the collaborative, distributed open science network, its effectiveness depends on understanding the relationships and linkages between system elements and achieving an appropriate balance between them. Research limitations/implications: The current research has focused on biomedicine. This research builds on the worldwide effort to reduce barriers, in particular paywalls to health knowledge. The findings present an opportunity to rationalize and improve a KMS integral to biomedical knowledge. Practical implications: Adoption of the KMS framework for a distributed, networked OBR will facilitate open science through reducing duplication of effort, removing barriers to the flow of knowledge and ensuring effective management of biomedical knowledge. Social implications: Achieving quality, permanency and discoverability of a region's digital assets is possible through ongoing usage of the framework for researchers, industry and consumers. Originality/value: The framework demonstrates the dependencies and interplay of elements and processes to frame an OBR KMS.